Early Detection of Growth and Development of Preschool Children in Transition Areas - Simeulu, Putro; Syamsuddin, Asniah; Hasniah, Hasniah; Hanum, Lathifah; Oetama, Saiful; Sitio, Roma; Ritawati, Ritawati (Poltekkes Kemenkes Aceh, 2025)
Background: Early detection of child growth and development plays a crucial role in ensuring children's readiness for formal education and preventing delays in intervention during the golden period of development. The reality in urban-rural transition areas shows that implementation is suboptimal due to low parental participation, limited teacher competency, and the limited availability of tested standardized instruments. Purpose: To describe the implementation of early childhood growth and development screening at Bungong Jaroe Kindergarten, Aceh Besar, and to identify factors related to the effectiveness of the screening. Methods: This descriptive research used a case study approach. The study population consisted of all children aged 4–6 years, teachers, parents, and PAUD administrators at Bungong Jaroe Kindergarten. Sampling used purposive sampling, including 20 children, 20 parents, 6 teachers, and 3 PAUD administrators, with inclusion criteria: children aged 4–6 years enrolled at Bungong Jaroe Kindergarten, teachers teaching for at least 1 year, and parents willing to be interviewed. Data collection was conducted through semi-structured interviews, observations, and document reviews. The screening instruments used included the Child Development Card (KKA) and the Developmental Pre-Screening Questionnaire (KPSP), which had previously been tested for validity and reliability. Data were analyzed using thematic analysis. Results: Implementation of growth and development screening at Bungong Jaroe Kindergarten is suboptimal, reflected in low parental participation only 50%, minimal teacher training, and limited use of standardized instruments. Children's nutritional status indicates a double burden of malnutrition, with 10% undernourished and 35% at risk of overnutrition. Factors related to screening effectiveness include teacher competence, parental awareness, instrument availability, and institutional support. Conclusion: Early detection of child growth and development at Bungong Jaroe Kindergarten remains limited. Strengthening teacher capacity, increasing parent participation, and developing an integrated monitoring system are needed to improve screening effectiveness.